ChemInform Abstract: One‐Pot Three‐Component Synthesis of New Mono‐ and Bis‐1, 2, 3‐triazole Derivatives of 2‐Benzimidazolethiol with a Promising Inhibitory Activity Against Acidic Corrosion of Steel. Issue 41 (7th October 2014) - Cruz‐Gonzalez, Deysi Y.; Gonzalez‐Olvera, Rodrigo; Negron‐Silva, Guillermo E.; Lomas‐Romero, Leticia; Gutierrez‐Carrillo, Atilano; Palomar‐Pardave, Manuel E.; Romero‐Romo, Mario A.; Santillan, Rosa; Uruchurtu, Jorge
Abstract The corrosion inhibition efficiency of the new heterocycles is investigated on steel grade API 5L X52 in 1M HCl employing electrochemical impedance spectroscopy.